Attitudes and practices regarding resuscitation in emergency departments in Trinidad and Tobago. Issue 11 (13th July 2013) - Baird, Georgia; Sammy, Ian; Nunes, Paula; Paul, Joanne
Abstract : Background: Ethical issues with regard to resuscitation are increasingly important. Understanding how emergency physicians deal with these problems is essential for the development of policies for resuscitative care. Objectives: To identify the knowledge, opinions and practices of emergency physicians employed full time in public hospitals in Trinidad and Tobago, with respect to cardiopulmonary resuscitation. To compare the differences in responses between physicians in training and those who were not. In addition, to compare these responses with those expressed in a similar study in the USA in 2007. Methods: All emergency physicians (120) who fulfilled the eligibility criteria for the study were asked to record anonymous responses to survey questions about ethical issues regarding resuscitation. Results: Of the 98 respondents, most (79.6%) had been practising emergency medicine for ≤5 years and about 38% had had some training in emergency medicine. Most respondents agreed that survival rates for cardiopulmonary resuscitation (CPR) were poor. However, 41.2% of respondents had performed CPR >10 times in the past 3 years despite expected futility. More participants in the US study than in the local study thought that the existence of an advance directive was important in making decisions about CPR and that legal concerns should not, but do, affect CPR decisions in practice. Conclusions: Local emergency physicians are as affected by legal and ethical CPR issues as are US emergency physicians. Education programmes and policies that deal with these concerns would better assist the emergency physician in dealing with them.